Health system costs of rheumatic heart disease care in South Africa - Assegid G. Hellebo; Liesl J. Zuhlke; David A. Watkins; Olufunke Alaba (BMC, 2021)
Abstract Background Rheumatic Heart Disease (RHD) is a disease of poverty that is neglected in developing countries, including South Africa. Lack of adequate evidence regarding the cost of RHD care has hindered national and international actions to prevent RHD related deaths. The objective of this study was to estimate the cost of RHD-related health services in a tertiary hospital in the Western Cape, South Africa. Methods The primary data on service utilisation were collected from a randomly selected sample of 100 patient medical records from the Global Rheumatic Heart Disease Registry (the REMEDY study) - a registry of individuals living with RHD. Patient-level clinical data, including, prices and quantities of medications and laboratory tests, were collected from the main tertiary hospital providing RHD care. All annual costs from a health system perspective were estimated in 2017 (base year) in South African Rand (ZAR) using a combination of ingredients and step-down costing approaches and later converted to United States dollars (USD). Step-down costing was used to estimate provider time costs and all other facility costs such as overheads. A 3% discount rate was also employed in order to allow depreciation and opportunity cost. We aggregated data to estimate the total annual costs and the average annual per-patient cost of RHD and conducted a one-way sensitivity analysis. Results The estimated total cost of RHD care at the tertiary hospital was USD 2 million (in 2017 USD) for the year 2017, with surgery costs accounting for 65%. Per-patient, average annual costs were USD 3900. For the subset of costs estimated using the ingredients approach, outpatient medications, and consumables related to cardiac catheterisation and heart valve surgery were the main cost drivers. Conclusions RHD-related healthcare consumes significant tertiary hospital resources in South Africa, with annual per-patient costs higher than many other non-communicable and infectious diseases. This analysis supports the scaling up of primary and secondary prevention programmes at primary health centers in order to reduce future tertiary care costs. The study could also inform resource allocation efforts and provide cost estimates for future studies of intervention cost-effectiveness.